Fluorescent Proteins for Flow Cytometry. Issue 1 (3rd April 2017) - Hawley, Teresa S.; Hawley, Robert G.; Telford, William G.
Abstract: Fluorescent proteins have become standard tools for cell and molecular biologists. The color palette of fluorescent proteins spans the ultraviolet, visible, and near‐infrared spectrum. Utility of fluorescent proteins has been greatly facilitated by the availability of compact and affordable solid state lasers capable of providing various excitation wavelengths. In theory, the plethora of fluorescent proteins and lasers make it easy to detect multiple fluorescent proteins simultaneously. However, in practice, heavy spectral overlap due to broad excitation and emission spectra presents a challenge. In conventional flow cytometry, careful selection of excitation wavelengths and detection filters is necessary. Spectral flow cytometry, an emerging methodology that is not confined by the "one color, one detector" paradigm, shows promise in the facile detection of multiple fluorescent proteins. This chapter provides a synopsis of fluorescent protein development, a list of commonly used fluorescent proteins, some practical considerations and strategies for detection, and examples of applications. © 2017 by John Wiley & Sons, Inc.